Job insecurity and job performance as the key research issues of the modern labor market - Wyrwa, Joanna; Łoś-Tomiak, Anna (Research Papers in Economics and Finance, 2023)
The analysis of the contemporary labour market requires consideration and multidimensional interpretation of the concept of "insecurity" in relation to employment and job retention, as well as changes in working circumstances. It points to correlations between the concept of uncertainty and work efficiency and time. This article aims to contribute to the understanding of the relationship between job insecurity and productivity by looking at two important research issues that have received relatively little empirical attention so far. An intra-individual model is presented here, combining job insecurity, understood as a more or less continuous and long-term stress factor, with work efficiency. It was pointed out that job insecurity changes over time, and employees achieve better professional results feeling confident in their future in the workplace. It presents the mechanisms underlying job insecurity and labour productivity. A thesis has been proposed according to which the relationship between job insecurity and self-assessment of work performance may be non-linear, or more precisely "U-shaped". According to this perspective, it has been suggested that job insecurity negatively affects work productivity by weakening occupational energy, the so-called vigor, enthusiasm for work. The article can be a starting point for further studies on the problem job insecurity.